Selected Issues of Arbitrability of Disputes Related to the Purchase of Goods for State and Municipal Needs - A. Yu. Piddubrivnaya (Теоретическая и прикладная юриспруденция)
The article highlights issues related to determining the jurisdiction of disputes related to the purchase of goods, works and services to meet state and municipal needs. The author comes to the conclusion that the law enforcement practice and the positions of the highest courts of the Russian Federation confirm the possibility of considering disputes arising from contracts related to supplies for state and municipal needs in the framework of arbitration proceedings.